Docosahexaenoic Acid Rescues Synaptogenesis Impairment and Long-Term Memory Deficits Caused by Postnatal Multiple Sevoflurane Exposures. (11th August 2016) - Tao, Guorong; Luo, Yan; Xue, Qingsheng; Li, Guohui; Tan, Yongchang; Xiao, Jinglei; Yu, Buwei
Abstract : Sevoflurane exposures were demonstrated to induce neurotoxicity in the developing brain in both human and animal studies. However, there is no effective approach to reverse it. The present study aimed to evaluate the feasibility of utilizing docosahexaenoic acid (DHA) to prevent sevoflurane-induced neurotoxicity. P6 (postnatal 6 days) mice were administrated DHA after exposure to 3% sevoflurane for two hours daily in three consecutive days. Molecular expressions of synaptic makers (PSD95, synaptophysin) and synaptic morphological changes were investigated by Western blot analysis and transmission electron microscopy, respectively. Meanwhile, Morris water maze test was used to assess spatial memory of mice at P31 (postnatal 31 days). DHA restored sevoflurane-induced decreased level of PSD95 and synaptophysin expressions and increased PSD areas and also improved long-term spatial memory. These results suggest that DHA could rescue synaptogenesis impairment and long-term memory deficits in postnatal caused by multiple sevoflurane exposures.